IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH ENGLISH SONG - Thessa Lonica Turang; Sanerita T. Olii; Paula Rombepajung (Program Studi Pendidikan Bahasa Inggris, 2022)
This study was conducted in the purpose to find out whether the use of English song can improve students’ vocabulary or not. This study was delimited on the teaching vocabulary particularly verb using English song to SMP Katolik Gonzaga Tomohon, especially second grade students in ongoing semester academic year of 2021/2022. More specifically, five songs entitled included in Disney Soundtracks were only used in this study considering the song difficulty and students’ level. Those are I See the Light, Reflection, A Whole New World, Let it Go, and Beauty and the Beast. The research design is pre-experimental design with one group pre-test and post-test. The second grade students of SMP Katolik Gonzaga Tomohon in the academic year 2021-2022 were the subjects of this study. The class consists of 31 students. The writer used multiple-choice test with pre-test, giving treatment with English song implementation and giving post-test in another multiple choice test. The data analysis shows that (a) the mean of the post-test 7.25 and the the mean of pre-test is 6.58, and (b) the standard deviation of the pre-test data is 0.87 whereas the post-test data is 0.79. These results of data analysis indicate that the students’ vocabulary mastery increases after being used English song as treatment. It means that the use of English song is effective in improving the students’ vocabulary mastery. The finding states that English song use is effective in improving students’ vocabulary mastery. Therefore, English teachers are suggested to take the use of English song into consideration as a useful alternative for teaching verb vocabulary.